Homelessness, Unsheltered Status, and Risk Factors for Mortality: A Comprehensive Review - Abdulkarim Yassien Almakki et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Homelessness, particularly unsheltered homelessness, is a severe public health issue linked to increased mortality rates. This review examines the association between homelessness and mortality, highlighting the unique challenges faced by unsheltered individuals. It explores key risk factors, including mental health disorders, substance abuse, chronic diseases, and environmental exposure. Additionally, it evaluates interventions aimed at mitigating mortality risks among homeless populations, emphasizing the need for integrated healthcare and social support systems. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/299 DOI: https://doi.org/10.5281/zenodo.14583384